A Late Paleozoic Hydrothermal Gold Mineralization Event in the Northern Margin of the North China Craton: Evidence of In Situ Apatite U‐Pb Dating and Hg Isotope Tracing of the Giant Hadamengou Gold Deposit - Tingting Xiao; Deyou Sun; Cheng Xu; Zhendong Tian; Anbo Luo; Changzhou Deng; Runsheng Yin (Geochemistry, Geophysics, Geosystems)
Abstract The northern margin of the North China Craton (NCC) hosts large numbers of hydrothermal gold deposits, with mineralization ages ranging from the Paleozoic to Mesozoic eras. The genesis of these deposits has been primarily ascribed to magmatic‐hydrothermal or crustal‐metamorphic fluid models. The Hadamengou gold deposit (>170 t Au), the largest gold deposit in this region in terms of gold reserve, is still unclear on either the mineralization age or the source of metals. In this work, in situ apatite (hydrothermal) U‐Pb dating and Hg isotope tracing were employed to address the two key issues. In situ apatite U‐Pb dating revealed a mineralization age of 335 ± 10 Ma (2SD), coinciding with the period of Paleo‐Asian Ocean subduction. Mercury isotope analyses yielded near‐zero Δ199Hg values (−0.01 ± 0.06‰, SD) in ores and sulfides, consistent with results for the nearby ∼360 to ∼330 Ma Dahuabei granitic pluton (−0.09 ± 0.03‰, SD), suggesting a close genetic connection between them. The results of this study support that the Hadamengou belongs to a Late Paleozoic hydrothermal gold mineralization system, which was formed closely related to subduction of the Paleo‐Asian Ocean. This study demonstrates a Late Paleozoic gold mineralization event and a good potential for exploration of gold around Late Paleozoic granitic plutons in the northern margin of the NCC.